Munch - Loshak, David
"Few images in the history of art are as widely recognized as Edvard Munch's The Scream. It conveys its powerful message very directly so that the viewer requires no knowledge of the circumstances of its creation to derive meaning form it. The quality of much on Munch's work means that although The Scream and several other images such as The Madonna are generally familiar, other aspects of Munch's life and work are little known or ignored. The influence Munch had on some younger artists with this expressionistic quality in his art has often led him being seen purely as a pioneer for Modernism. David Loshak demonstrates that to see munch only in these terms is to misunderstand his art. Just as Raphael, an eclectic who borrowed from predecessors and contemporaries, brought the humanistic tradition of the Italian Renaissance to one of the peaks of its development, so Munch, also an eclectic, also did something similar for the realistic-romantic tradition of the nineteenth century. For a long time he seemed to be turning his back to realism, whereas actually, on a deeper level, unlike some contemporaries from whom he borrowed what he needed, he was not rejecting, but extending it, adding rather than substituting a new dimension of subjectivity..."--